Prospective interventional study of staple line reinforcement and buttressing in laparoscopic sleeve gastrectomy - Gedam, Manik C.; Tayade, Priyanka C. (International Surgery Journal, 2020)
Background: Laparoscopic sleeve gastrectomy has gained increasing acceptance among bariatric surgeons and patients. The three main options for staple line reinforcement are over-sewing and buttressing with synthetic polymers or biologic tissue. The purpose of this study was to prospectively analyse the relative efficacy of gastric staple line reinforcement (SLR) by using over sewing as the method of reinforcement and comparing it with non-reinforcement laparoscopic sleeve gastrectomy (LSG) in 60 patients who were admitted in IGGMC Nagpur from May 2017 to November 2019. Methods: Obese patients with age 18-65 years, BMI 40 and above with-out co-morbidities and 35 and above with co-morbidities, and BMI below 60, with no malignancy, no hiatus hernia, no previous bariatric procedure were included. All patients underwent LSG after thorough evaluation. 30 patients had reinforced staple line, while 30 had simple staple line. Results: Total 60 patients were studied, 30 in each group. Intraoperative leak was seen in 1 patient each in both study groups. No bleeding was seen in reinforced LSG, while 3 patients had intraop bleeding in simple staple line group. 1 patient each of non-reinforced group had postop leak, postop bleeding and post op morbidity and mortality in 1 patient, while no postop leak or bleeding, morbidity or morality was seen in reinforced group. Conclusions:Reinforcement of staple line by over sewing in LSG resulted in significantly fewer surgical complications, lesser morbidity and no mortality compared to simple stapling of the gastric tube.